Implementing a clozapine supply service in Australian community pharmacies: barriers and facilitators - Bethany Wilson; Sara S. McMillan; Amanda J. Wheeler (Taylor & Francis Group, 2019)
Background Clozapine is the most effective antipsychotic for treatment-resistant schizophrenia, although serious adverse effects such as agranulocytosis and cardiomyopathy limit its use. In July 2015, Australian regulations changed to allow community-based prescribing and supply of clozapine for maintenance therapy. However, there is currently no information on the rate of clozapine services available in Australian community pharmacies, or the factors that influence a pharmacist's decision to provide, or not provide, a clozapine service, particularly from the perspective of those pharmacists who do not offer this service. This study investigated Australian community pharmacies providing a clozapine supply service and the barriers to, and facilitators of, implementing this service. Methods This mixed method exploratory study was conducted in two stages: (1) a brief online survey of community pharmacists Australia-wide; and (2) semi-structured telephone interviews. The survey was conducted between November 2017-January 2018; results were analysed via descriptive statistics. Survey respondents who did not provide a clozapine service were eligible to participate in a telephone interview exploring barriers and facilitators. Interviews were undertaken between December 2017-January 2018 and data analysed thematically. Results A total of 265 pharmacists completed the survey; 51.3% (n = 136) provided a clozapine service. Consumer demand was a key facilitator (n = 18/247; 66.1%) and the main barrier to implementing a clozapine service was a perceived lack of need (n = 70/122; 57.4%). Twelve survey respondents were interviewed; while most participants acknowledged that supplying clozapine in community pharmacies would benefit consumers due to convenience, the lack of training and support led to difficulties in service implementation. Conclusions Although regulatory changes aimed to improve access to clozapine, it is unclear if they have been successful, or to what degree. Community pharmacists were positive about supplying clozapine in the community but identified a need for training and support to raise awareness of the service so that eligible clozapine consumers can be transitioned to community-based care. Further research is needed about the perceptions of clozapine consumers to determine whether the regulatory changes have resulted in positive outcomes for their independence and quality of life.